Kommentierte Checkliste der Pyraloidea von den Azoren, mit der Beschreibung von drei neuen Arten (Lepidoptera: Pyraloidea). - Meyer, Marc; Nuss, Matthias; Speidel, Wolfgang (Contributions to Entomology = Beiträge zur Entomologie, 1997)
Twenty species of Pyraloidea (excl. Scopariinae) are presently known to occur in the Azores. The distribution of each species on the different islands is indicated. Three new species are described: Homoeosoma miguelensis sp. n., Homoeosoma picoensis sp. n., Udea azorensis sp. n. and three new generic combinations are given: Udea atlanticum (Bethune-Baker, 1894) comb. n. (Botys) and Udea maderensis (Bethune-Baker, 1894) comb. n. (Botys), both endemic on Madeira; Udea nordmani (Rebel, 1937) comb. n. (Pionea), endemic on the Canary Islands. Possible pathways of immigration are discussed. Nomenclatural Acts miguelensis Meyer, Nuss & Speidel, 1997 (Homoeosoma), spec. n. picoensis Meyer, Nuss & Speidel, 1997 (Homoeosoma), spec. n. atlanticum (Bethune-Baker, 1894) (Udea), comb. n. hitherto Botys atlanticum azorensis Meyer, Nuss & Speidel, 1997 (Udea), spec. n. maderensis (Bethune-Baker, 1894) (Udea), comb. n. hitherto Botys maderensis nordmani (Rebel, 1937) (Udea), comb. n. hitherto Pionea nordmani